Desain Ruang Pengering Hybrid untuk Peningkatan Kualitas Tembakau di Desa Kajoran: Indonesia - Purwiandono, Gani; Wiranto, Yudi; Aprianto, Lukman (UII, 2026)
Kajoran Village is one of the main tobacco-producing areas in Karanggayam District, Kebumen Regency, Central Java Province. However, farmers often face challenges in the tobacco drying process, which is highly dependent on weather conditions, especially during the rainy season, leading to reduced quality and lower selling prices. Through a Community Service Program (KKN), a participatory approach was carried out using field observations, needs analysis, and technology design to develop a hybrid-based tobacco drying room. This system combines natural heat from sunlight with alternative energy generated from the combustion of tobacco stalk waste. The drying room was designed using ArchiCAD software with dimensions of 343 meters and equipped with eight layers of trays. The scope of the design includes a maximum drying capacity of 100 kg of wet-cut tobacco per cycle and the use of locally available materials. The outcomes of this program include a physical design of the drying room, a drying process algorithm, and technical guidelines that can be independently implemented by the Kajoran Village community to enhance the efficiency and quality of tobacco drying.